Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Certainly! Let's solve the given equations step-by-step to find [tex]\(\frac{a}{b}\)[/tex].
Given:
1. [tex]\(\frac{a+c}{b} = \frac{3}{2}\)[/tex]
2. [tex]\(\frac{b}{c} = \frac{3}{4}\)[/tex]
First, let's deal with the second equation to express [tex]\(c\)[/tex] in terms of [tex]\(b\)[/tex]:
[tex]\[ \frac{b}{c} = \frac{3}{4} \][/tex]
This implies:
[tex]\[ b = \frac{3}{4}c \][/tex]
To solve for [tex]\(c\)[/tex]:
[tex]\[ c = \frac{4}{3}b \][/tex]
Now, substitute [tex]\(c = \frac{4}{3}b\)[/tex] into the first equation:
[tex]\[ \frac{a + c}{b} = \frac{3}{2} \][/tex]
[tex]\[ \frac{a + \frac{4}{3}b}{b} = \frac{3}{2} \][/tex]
We can split this fraction:
[tex]\[ \frac{a}{b} + \frac{\frac{4}{3}b}{b} = \frac{3}{2} \][/tex]
[tex]\[ \frac{a}{b} + \frac{4}{3} = \frac{3}{2} \][/tex]
Subtract [tex]\(\frac{4}{3}\)[/tex] from both sides:
[tex]\[ \frac{a}{b} = \frac{3}{2} - \frac{4}{3} \][/tex]
To subtract these fractions, we need a common denominator. The common denominator of 2 and 3 is 6:
[tex]\[ \frac{3}{2} = \frac{9}{6} \][/tex]
[tex]\[ \frac{4}{3} = \frac{8}{6} \][/tex]
Now, subtract the fractions:
[tex]\[ \frac{a}{b} = \frac{9}{6} - \frac{8}{6} = \frac{1}{6} \][/tex]
Thus, the ratio [tex]\(\frac{a}{b}\)[/tex] is:
[tex]\[ \frac{a}{b} = \boxed{\frac{1}{6}} \][/tex]
Given:
1. [tex]\(\frac{a+c}{b} = \frac{3}{2}\)[/tex]
2. [tex]\(\frac{b}{c} = \frac{3}{4}\)[/tex]
First, let's deal with the second equation to express [tex]\(c\)[/tex] in terms of [tex]\(b\)[/tex]:
[tex]\[ \frac{b}{c} = \frac{3}{4} \][/tex]
This implies:
[tex]\[ b = \frac{3}{4}c \][/tex]
To solve for [tex]\(c\)[/tex]:
[tex]\[ c = \frac{4}{3}b \][/tex]
Now, substitute [tex]\(c = \frac{4}{3}b\)[/tex] into the first equation:
[tex]\[ \frac{a + c}{b} = \frac{3}{2} \][/tex]
[tex]\[ \frac{a + \frac{4}{3}b}{b} = \frac{3}{2} \][/tex]
We can split this fraction:
[tex]\[ \frac{a}{b} + \frac{\frac{4}{3}b}{b} = \frac{3}{2} \][/tex]
[tex]\[ \frac{a}{b} + \frac{4}{3} = \frac{3}{2} \][/tex]
Subtract [tex]\(\frac{4}{3}\)[/tex] from both sides:
[tex]\[ \frac{a}{b} = \frac{3}{2} - \frac{4}{3} \][/tex]
To subtract these fractions, we need a common denominator. The common denominator of 2 and 3 is 6:
[tex]\[ \frac{3}{2} = \frac{9}{6} \][/tex]
[tex]\[ \frac{4}{3} = \frac{8}{6} \][/tex]
Now, subtract the fractions:
[tex]\[ \frac{a}{b} = \frac{9}{6} - \frac{8}{6} = \frac{1}{6} \][/tex]
Thus, the ratio [tex]\(\frac{a}{b}\)[/tex] is:
[tex]\[ \frac{a}{b} = \boxed{\frac{1}{6}} \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.